Lab-Sophistication: Does Repeated Participation in Laboratory Experiments Affect Pro-Social Behaviour? - Tiziana Medda; Vittorio Pelligra; Tommaso Reggiani (Masaryk University, Faculty of Economics and Administration, 2021)
Experimental social scientists working at research-intensive institutions deal inevitably with subjects who have most likely participated in previous experiments. It is an important methodological question to know whether participants that have acquired a high level of lab-sophistication show altered pro-social behavioral patterns. In this paper, we focus both on the potential effect of the subjects' lab-sophistication, and on the role of the knowledge about the level of lab-sophistication of the other participants. Our main findings show that while lab-sophistication per se does not significantly affect pro-social behaviour, for sophisticated sub-jects the knowledge about the counterpart's level of (un)sophistication may systematically alter their choices. This result should induce caution among experimenters about whether, in their settings, information about lab-sophistication can be inferred by the participants, due to the characteristics of the recruitment mechanisms, the management of the experimental sessions or to other contextual clues.
Keywords: D03; D83; C91; C92; 330; Lab-sophistication; Experimental Methodology; External Validity; Pro-social behaviour; Cooperation